If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -1h = 6gk + 11 Reorder the terms: 3 + -1h = 11 + 6gk Solving 3 + -1h = 11 + 6gk Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1h = 11 + -3 + 6gk Combine like terms: 3 + -3 = 0 0 + -1h = 11 + -3 + 6gk -1h = 11 + -3 + 6gk Combine like terms: 11 + -3 = 8 -1h = 8 + 6gk Divide each side by '-1'. h = -8 + -6gk Simplifying h = -8 + -6gk
| -18u-12=-30u-18 | | 8-7w=3w+9 | | 2x^2-20x+49=0 | | 3x+11=-5 | | -1=5(w-2)-8w | | 3(x+3)+3x=27 | | 49y^2-14xy+x^2=0 | | 8-3=7-3-3 | | (10)=x | | .5(18+4h)h=26 | | 10+2=x | | -34=7(y-7)-4y | | 5x-35=-12x | | 12(3x+4)-7(2x-5)=2x-57 | | 6y+7=3y-14 | | 5x-12=83 | | -10x-7=9 | | 5w-12=33 | | x-2+2x=-2+9x | | 0.2w-4.7=-2.2w+4.9 | | 12-5w=33 | | h=80t-16t^2 | | -7v+16=-5v+10 | | 9(3x+4)=7(x+4)+20 | | 50=8+2x | | 6x-12(x+1)=-6+22 | | 3x=5y+17 | | 0.1+x+0.5=0 | | 50=8+x/2 | | (-5.3)(1.9)(3.6)= | | 6x+5-4(x+1)=9x+7 | | 7a+5=54 |